Still Unanswered Questions About SARS-CoV-2 Mortality and Future Directions for Occupational Medicine - Zocchetti, Carlo; Bonzini, Matteo (La Medicina del Lavoro, 2023)
The article discusses a recent study on mortality attributable to COVID-19 in Italy and the need for further analysis. The study used a reliable methodology to estimate excess deaths due to the pandemic. However, there are still questions about the specific effects of COVID-19 compared to other factors, such as delayed or missing access to treatment for other illnesses. Analyzing the time course of excess deaths could reveal such effects. There are also open questions about how COVID-19 deaths are classified and reported, which could lead to over or under-diagnosing cases. The article notes that occupational physicians have played an important role in preventing the spread of COVID-19 among workers. A recent study found that personal protective equipment (PPE), particularly masks, effectively reduced the risk of infection among healthcare workers. However, it is still unclear whether Occupational Medicine should incorporate infectious diseases as a major concern or return to its historically agnostic attitude toward communicable diseases. More data on mortality from specific diseases will be needed for further analysis and understanding of the pandemic's effects on mortality rates in Italy.